Pemberdayaan Masyarakat Dusun Jogonalan Melalui Pengelolaan Lingkungan dan Penguatan Pendidikan - Kamil, Muhamad; Pramudya, Adzin Hafidh; Khomunissah, Ainun Fitri; Yuliana, Susi; Septarianto, Redi; Nasabandi, Syah Awat; Fitri, Inaya Erwansyah; Kholmi, Masyah; Sloka, Rizqi Jagad; Darmawati, Idiani (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Integrated waste management activities in Jogonalan Hamlet, Kulonprogo have been implemented through a waste sorting system based on three main categories-organic, non- organic, and B3, which is the result of collaboration between Students of Community Service Program Universitas Muhammadiyah Yogyakarta and Kulonprogo Waste Bank Parent. The program began with a socialization and workshop presented by Mr. Sugiyanto, Director of Induk Bank Sampah Kulonprogo, who emphasized the importance of applying the 3R principles (Reduce, Reuse, Recycle) and building a network of waste banks at the village and hamlet level. The implementation of the program is in the form of education to the community about the use of technology such as Google Maps to map the location of waste banks and digital savings book applications to record waste savings balances, as well as the importance of the involvement of various parties such as PKK, Farmers Groups, Women Farmers Groups, Pokdakan, Takmir Masjid, Karang Taruna, MSMEs, and PAUD in supporting a sustainable waste management system. The results of the activities show a significant increase in community awareness and participation in sorting waste, especially non-organic waste that has a selling value, although the main challenge in this program is to change the mindset and habits of the community to consistently sort waste, with the program's strengths lying in increasing community understanding that waste can be an economic source and the importance of individual roles in creating a cleaner environment, so it is hoped that with continued education and assistance, an integrated waste management system can become an integral part of the daily lives of the people of Jogonalan Hamlet